Food survival strategies in Congoles refugees and Asylum seekers communities in Johannesburg - Mupenda, Mutuza Lupepe Jacques (My University, 2018)
In recent decades, several studies on food insecurity have been conducted in developing countries to understand how poor households develop livelihood strategies for accessing food and other basic needs. In Johannesburg, there are studies that have attempted to assess how poor households, including households of cross-border migrants, are adopting coping strategies to access food. However, it still seems difficult to find any study that has focused particularly on the food survival strategies of Congolese forced migrants living in Johannesburg. Yet, Congolese refugees and asylum seekers living in Johannesburg are part of the forced migrants who face serious difficulties in developing sustainable livelihoods and are often victims of discrimination, exclusion and xenophobia. Therefore, it was essential to carry out this study to evaluate the food survival strategies of Congolese refugees and asylum seekers living in Johannesburg. A cross-sectional household-based study was conducted in a sample of 76 households, of which 36 households were in Rosettenville and 40 households were in Yeoville. The snowball sampling technique was used to select potential households. Participation in the survey was free and voluntary. The face-to-face paper interviews were conducted between the interviewer and the participants. The interviews with the respondents were based on the socio-demographic and socio-economic profiles of households, livelihoods, food sources, coping strategies, and food survival strategies. The collected data were analysed through the thematic method. The results of this study revealed that the vast majority of households were headed by men, and most households were made up of related members. In some households, there were married people who lived as household members. Most household members had immigrated to South Africa to improve their living conditions and only a limited number of household members held a refugee status. Several household members also had a good level of education. The unemployment rate was also considerable in sampled households, and it was found that women constituted the largest proportion of the unemployed. These women were more active in the informal economy. It was noted that government grants and social assistance for the reduction of poverty and income inequality were exclusively granted to household members who held refugee status. There were also women who rely on prostitution to improve the household income, and some households used their children, who were under the age of 18 years, to generate household income. It is evident that most households have the socio-demographic and socio-economic profiles of households that are experiencing serious difficulties in accessing healthy and sufficient food. Similarly, most households did not have the resources to buy food of their choice. In addition, a significant number of households were adopting severe food survival strategies to have access to food. Nevertheless, it is important to note that government grants and social assistance are available to Congolese refugees and asylum seekers in Johannesburg. Similarly, it is necessary to help female members to access formal credit. In addition, it is important that the South African government makes an effort to combat discriminatory patterns of exclusion and xenophobia, which most Congolese refugees and asylum seekers face. This is to help reduce poverty and income inequality for Congolese refugees and asylum seekers in Johannesburg. This will in turn allow them to have access to safe and adequate food. Keywords: rapid urbanisation, food security, household food security, livelihood, coping strategies, Congolese refugee and asylum seekers, Johannesburg, food survival strategies, poverty, discrimination, exclusion, xenophobia
A thesis submitted in partial fulfilment of requirement for the Degree of Master of Science, School of Geography, Archaeology and Environmental Studies, Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa Johannesburg 2018
Keywords: Congolese (Democratic Republic)--South Africa; Refugees--South Africa--Social conditions; Political refugees--South Africa--Social conditions